Menumbuhkan Siswa Sebagai Warga Global Melalui Media Interaktif Di Sekolah Dasar - Yuli Adhani; Candra Cuga; Pratiwi Pratiwi (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2021)
The development of civic education content and learning processes in elementary schools is significant to proportionally accommodate global issues so that students can play a role as citizens and like global citizens. Various approaches and media are being developed. One of them is gamification-based interactive thematic learning media. In previous studies, an analysis of Civics learning at SDN 38 Hulonthalangi was carried out as a vehicle for the formation of students as citizens of the world. The research found a picture of the learning that was not optimal in developing student competencies as global citizens. So that the author conducts collaborative research with students in developing interactive learning media and produces interactive multimedia designs in the form of an Android-based application to know the world. This study aims to develop media and content-oriented to the Basic Competencies of Civics in the Globalization Theme in Class VI, by adopting and modifying Thiagarajan's research methods, namely define, design, develop, and dissimination. The results of this study are to test the feasibility of the application, namely by validating the application to a team of experts and has obtained an average percentage value of 93.05% for media and 93.75% for the material. Based on the results of this study, an Android-based application to know the world is very suitable to be used in the process of learning the theme of globalization for class VI and is believed to be part of the process of preparing students as global citizens in elementary schools.